A Cross-Sectional Study on the Relationship Between Nurse Motivation and The Implementation of Discharge Planning for Patients with Diabetes Mellitus - Rahmawati Shoufiah; Aji Yudha Yudistira; Rizky Setiadi; Hilda Hilda; Lukman Nulhakim (Poltekkes Kemenkes Palu, 2025)
In 2020, the Indonesian Ministry of Health reported that only 35% of 119,665 post-hospital care patients returned to follow-up on their condition and one of the influencing factors is the implementation of discharge planning which has not yet been optimized. The implementation of discharge planning requires high motivation from a nurse to achieve a good result. This study aimed to determine the relationship between nurse motivation and implementation of discharge planning in patients with diabetes. This is a quantitative analytical cross-sectional study. The population in this study was all executive nurses, totaling 71 respondents in the internal medicine and surgical inpatient rooms of Government Hospitals in Kutai Kartanegara. The sampling method used was total sampling. The instruments used were nurse motivation questionnaires and discharge planning. Majority of the respondents were female (67.6%), aged ≥ 25 (70.4%) with a bachelor’s degree in nursing (64.8%) an a lenght of work ≥5 years (78.9%). There was a relationship between nurse motivation and the implementation of discharge planning in DM patients with p-value 0.001 (AOR: 9.6 (95% CI: 3–31)) after adjusting for length of work, education level, and age. This study proves that high nurse motivation affects the implementation of discharge planning in patients with Diabetes Mellitus.